Mediação de leitura por professores do AEE junto a crianças com deficiência intelectual - Santos, Dayane Ribeiro dos (2024)
This study aimed to analyze the reading mediation of Specialized Educational Assistance (SEA) teachers, using the infant light of knowledge software (ILK), with children with Intellectual Disability (ID) enrolled in Multifunctional Resource Rooms (MRR) in the Municipal Public Schools of Fortaleza. Specifically, it aimed to identify the reading mediations employed by SEA teachers that favored or hindered the progress of reading in their respective children and to investigate the resources and/or materials used by these teachers during reading mediation activities through the use of this software. A data subset from an umbrella action research field study, with a socio-interactionist qualitative approach, conducted by the Language and Rewritten Writing Group (LER) at UFC in 2018, was employed. In the original research, ten ILK software sessions were conducted, during which four SEA teachers mediated reading and writing activities with eight children with Intellectual Disability (ID). For this current study, two teachers (Bruna and Carla) and six children, three from each teacher, participated. Methodological procedures included selecting two sessions (S1 - S9) from the Reading module of the ILK software (beginning and end of the study) and analyzing data obtained from the initial and final reassessments of the six children. It was observed that the teachers employed distinct mediations during their actions, influencingading the reading development of the children. Various resources and/or materials, such as cards, images, and papers, were used by the teachers during these mediations. These resources and/or materials contributed to the children's reading development by assisting in the written interpretation of words/texts. In conclusion, intentional and purpose-defined reading mediations positively affect reading development. It is believed that such mediations should go beyond the limits of a specific proposed activity and respect the child's potential, motivating them to reflect on their own learning.